Assessment of Bacteriological Quality of Drinking Water in Taiz and Ibb Governorates, Yemen - Al-Hadheq, Ali Ahmed; Edrees, Wadhah Hassan; Al-Abboud, Mohammmed; Al-Arabi, Abdualhafeed; Al-Maktari, Mohammed; Al-Shehari, Wadee Abdullah; Al-Badani, Inan; Al-Asbahi, Baseem; Al-Ofairi, Bashir Ahmed (PSM Microbiology, 2024)
This study aimed to assess and monitor the safety and quality of the existing water supplies in Ibb and Taiz governorates from the microbial side and compare it with the World Health Organization. The water samples (99 samples) taken from some water sources, distribution reservoirs, and different regions were studied for bacteriological analysis, in which they were inoculated into culture media using two methods: the presumptive test for the most probable number and the confirmatory test for bacterial identification. The results indicated the non-existence of indicator bacteria that were used to indicate the possible presence of fecal bacteria among 24 (24.24%) water samples taken from Taiz governorate, while the presence of an unacceptable number of Escherichia coli in house tanks (30%) was indicated among 75 (74.25%) water samples taken from Ibb governorate. The results of the study in Taiz governorate show that the water is fit for human consumption, as well as the samples taken from water sources and distribution networks in Ibb governorate, but the results of the samples taken from house tanks showed that the water is not fit for human consumption and needs to be treated.